HUBUNGAN INSOMNIA DENGAN LAMA PASIEN MENJALANI HEMODIALISIS REGULER DI RSUD KABUPATEN LOMBOK UTARA BULAN JANUARI-JUNI TAHUN 2022 - I Putu Restu Surya Peraupan; Kadek Dwi Pramana; Hilda Santosa; Danang Nur Adiwibawa (Yayasan Nusantara Hasana Berdikari, 2023)
Chronic kidney disease (CKD) is a health problem whose incidence continues to increase. CKD causes high morbidity and mortality so that patients with CKD are required to get handlers to improve the patient's quality of life. Hemodialysis is a process of filtering or cleaning blood through a semi-permeable membrane which is performed on patients with impaired kidney function, both chronic and acute. While the patient is undergoing hemodialysis, there are complications experienced by the patient, one of which is insomnia. The aims to determine the relationship between length of time undergoing hemodialysis and insomnia in CKD patients at North Lombok District Hospital in January-June 2022. Research using cross sectional study design. The sampling technique was purposive sampling with data collection using a questionnaire with a total sample of 37 people. The results of the spermaman rank analysis obtained a p value of 0.005 (p <0.05), meaning that there was a relationship between the length of time undergoing hemodialysis and insomnia in CKD patients in North Lombok Regency in some patients undergoing hemodialysis for > 6 months (75.7%) and experiencing severe insomnia by 51.4%.